Sectoral building codes and their place in the new system of normative base on the basis of the parametric method - Isaienko, D.; Omelyanenko, М. (Ways to Improve Construction Efficiency, 2019)
In the article discribes the need for revision of sectoral building codes that are in force in the field of construction now. Cause the parametric method for determining regulatory requirements are implemented. The main requirements of sectoral building codes are analyzed. Results of this are proposals for their processing into other types of documents that was formed taking into account the implement of a parametric method for determining regulatory requirements.